Emotional Marketing is an Approach to Customer Happiness" an Exploratory Study of the Opinions of a Sample of Customers of Travel and Tourism Companies in the City of Mosul - Dr. Hend Khader Al-Qaisi; Dr. Layla Garallah Khaleel (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Purpose: The research aims to clarify the relationship between emotional marketing as an independent variable and customer happiness as a dependent variable, It was applied to a group of customers of travel and tourism companies in the city of Mosul. Theoretical framework: The two researchers reviewed relevant references and research to crystallize the work of the theoretical framework to complete this study. Design/methodology/approach: The two researchers applied the survey method Using a random sample of customers of travel and tourism companies in the city of Mosul; to collect primary data; Using (five Likergraded questionnaire). Findings: The study findings cleared that emotional marketing has a significant impact on customer happiness. Therefore, it is necessary to better train employees in order to provide better service to these customers. Research, Practical & Social implications: supporting the final findings of this study Results of other studies. It is clear that customers have increased their happiness when dealing with these companies because they have marketed the service emotionally to them. The results indicated that The need for the organization to focus on marketing campaigns to inform the customer of all new and innovative services. Originality/value: This study didn't contain any part of any other published study of any other person, nor materials which has been accepted for possessing any scientific degree of any university.